Avaliação da qualidade do sono, sono, sonolência diurna e transtornos do sono em pacientes com esclerose lateral amiotrófica do tipo 8 em comparação à forma esporádica e controles saudáveis - Tiago Felipe Vasconcelos Gonçalves (2022)
Introduction: Amyotrophic lateral sclerosis (ALS) is a rare and progressive neurological disease, still incurable, that primarily affects neuronal cells responsible for the voluntary control of skeletal muscles. A subtype of the disease, amyotrophic lateral sclerosis type 8 (ALS-8), was identified in families living in Zona da Mata region of Minas Gerais. There is a lack of studies on the disease, especially in relation to possible sleep-related disorders that may have their own characteristics. Objective: to investigate and compare the sleep quality of patients diagnosed with ALS-8, sporadic amyotrophic lateral sclerosis (ALS-s) and a control group. Methods: a cross-sectional, translational, non-interventional study, through the application of the Epworth Sleepiness Scale (ESS), Berlin Questionnaire, STOP-Bang, Pittsburgh Sleep Quality Index (PSQI), questioning about sleep-related nocturnal movements and Scale Functional Amyotrophic Lateral Sclerosis (ALSFRS). Results: the sample consisted of patients diagnosed with ALS-8 (n=17, 9 women, mean age 50 years), ALS-e (n=24, 10 women, mean age 58 years) and controls (n=24, 18 women, average age 50 years). The control group was sleepier than the ELA-8 group on ESS (p < 0.006). Obstructive sleep apnea (OSA) screening questionnaires did not show statistically significant differences between groups (Berlin p < 0.340 and STOP-Bang p < 0.456). The sleep quality measured by the PSQI was worse in the ELA-e group (11.7±5.4), followed by the ELA-8 (7.8±3.5) and better in the control group (5.3±3, 4), with a significant negative correlation with functionality ALSFRS (p<0.001; CC = -.503). In addition, ELA-8 patients had a higher frequency of complaints related to sleep-related nocturnal movements than participants in the control group (p<0.014). Conclusions: patients diagnosed with ALS-e and ALS-8 had worse sleep quality compared to controls, which seems to be related to reduced functionality. Patients with ALS-8 exhibit nocturnal movements similar to REM Sleep Behavior Disorder (REMSBD) parasomnia.